2021
DOI: 10.1186/s40510-021-00385-1
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the prefabricated forms of NiTi archwires on orthodontic forces delivered to the mandibular dental arch

Abstract: Background Although preformed archwires with a variety of arch forms are currently commercially available, the effects of variation in the shape of these archwires on the orthodontic force at each tooth are not well understood. Therefore, we evaluated the forces delivered by various types of commercially available preformed nickel–titanium alloy (NiTi) archwires in a simulated mandibular dental arch. Methods Sixty-three types of 0.019 × 0.025-inch … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 30 publications
(60 reference statements)
0
2
0
Order By: Relevance
“…In 2020 and 2021, 32 and 52 articles were published, respectively. The addressed topics were mainly wire properties on comparison of resistance,[ 18 19 ] clinical applications,[ 20 21 ] surface morphology,[ 22 23 ] activated forces,[ 24 25 ] and esthetic wires. [ 26 ] Such interest in properties is also noticed with the increasing number of researches comparing types of retainers (10 articles), three published in 2020 and four in 2021.…”
Section: Discussionmentioning
confidence: 99%
“…In 2020 and 2021, 32 and 52 articles were published, respectively. The addressed topics were mainly wire properties on comparison of resistance,[ 18 19 ] clinical applications,[ 20 21 ] surface morphology,[ 22 23 ] activated forces,[ 24 25 ] and esthetic wires. [ 26 ] Such interest in properties is also noticed with the increasing number of researches comparing types of retainers (10 articles), three published in 2020 and four in 2021.…”
Section: Discussionmentioning
confidence: 99%
“…11 Several studies have shown that there is a tendency for the inter-canine width to increase even with the use of light round nickel-titanium alloy (NiTi) archwires. 12 Open coil spring application and inerproximal disking were performed to obtain sufficient space for alignment of lateral incisors in maxillary and mandibular arches.…”
Section: Discussionmentioning
confidence: 99%